KONSELING INDIGENOUS DALAM MASA NEW NORMAL - Prasasti, Suci (Widya Wacana: Jurnal Ilmiah, 2020)
The impact of the spread of Covid -19 is not only a health problem but the impact of its spread has damaged the structure and aspects of life in society, causing economic, political, social, cultural and even educational problems. The problem is that during the new normal period, many people did not heed the appeal of the government, the community assumed that disease originated from God and if sickness was due to God's will. This is a very wrong assumption.Indgenious counseling is a solution in helping people to deal with the realities and problems of life by using the local cultural approach of the individual originating. In living, individuals cannot be separated from their inherent socio-culture. Individuals bring culture and counselors must be able to understand that culture. Individuals will feel comfortable and respected if the counselor can fit into the client culture.Keywords : Counseling, Indigenous, New NormalABSTRAKDampak penyebaran Covid -19 bukan hanya merupakan persoalan kesehatan saja tetapi dampak penyebarannya telah merusak tatanan dan asepek kehidupan di masyarakat sehinggan menimbulkan persolan ekonomi, politik, sosial, budaya bahkan pendidikan. Permasalahannya adalah pada masa new normal banyak masyarakat yang tidak mengindahkan himbauan pemerintah, masyarakat mempunyai anggapan bahwa penyakit berasal dari Tuhan dan seandainya sakit itu karena kehendak Tuhan. Ini adalah anggapan yang sangat keliru besar. Konseling indgenious merupakan salah satu solusi dalam membantu manusia menghadapi relialitas dan permasalahan kehidupan dengan menggunakan pendekatan budaya lokal individu berasal. Dalam berkehidupan, individu tidak bisa di lepaskan dari sosial budayanya yang telah melekat. Invidividu membawa budaya dan konselor harus bisa memhami budaya tersebut. Individu akan merasa nyaman dan di hormati apabila konselor bisa masuk dalam budaya klien.Â Kata Kunci : Konseling, Indigenous, New NormalÂ